Limiting case of the boundedness of fractional integral operators on nonhomogeneous space. (28th September 2006) - Sawano, Yoshihiro; Sobukawa, Takuya; Tanaka, Hitoshi
Abstract : We show the boundedness of fractional integral operators by means of extrapolation. We also show that our result is sharp.